Effect of Hydrodynamic Shear on Proteoglycan 4 Secretion by Bovine Cartilage Explants - Morin, Alyssa; Regmi, Suresh; Schmidt, Tannin (CMBES Proceedings, 2016)
Proteoglycan 4 (PRG4) is a mucin-like glycoprotein present in synovial fluid and at the surface of articular cartilage. PRG4 exists as both monomeric and disulfide-bonded multimeric forms, which are secreted by chondrocytes in bovine cartilage explants. Dynamic shear stimulation of cartilage explant cultures has been shown to increase PRG4 mRNA expression levels, the quantity of high molecular weight PRG4 species and overall PRG4 secretion compared to unloaded controls. However, the effect of hydrodynamic shear on the secretion of PRG4 by chondrocytes in vitro remains to be determined. Therefore, the objective of this study was to compare the quantity and immunoreactive size distribution of PRG4 products secreted into medium by chondrocytes in bovine cartilage explants from stirred bioreactor (Shear+) versus T-flask (Shear–) cultures. Indirect enzyme-linked immunosorbent assay was used to quantitatively assess the amount of PRG4 in Shear+ and Shear– media compared to a standard of purified full-length recombinant human PRG4. The immunoreactive size distribution of PRG4 proteins in Shear+ and Shear– media was assessed using sodium dodecyl sulfate polyacrylamide gel electrophoresis followed by western blot detection using anti-PRG4 antibodies 4D6 and 9G3. The amount of PRG4 accumulated in Shear+ media was significantly greater than Shear– media (p<0.001), with no detectable difference in immunoreactive size distribution. These results demonstrate that the secretion of PRG4 by chondrocytes in vitro is regulated, in part, by hydrodynamic shear, and further contribute to the understanding of mechanical regulation of PRG4 expression.